2014
DOI: 10.1136/heartjnl-2013-304916
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between sex, early valve surgery and mortality in patients with left-sided infective endocarditis analysed in a population-based cohort study

Abstract: Women underwent EVS less often than men. However female sex was independently associated with neither EVS nor 1-year mortality. The reasons for a higher risk of early postoperative mortality in women must still be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
7
39
2
Order By: Relevance
“…The male predominance in IE has been well-documented 11 20. Furthermore, we found that the proportion of females was higher in the MVE than in the AVE group, which was also previously reported 11 21.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The male predominance in IE has been well-documented 11 20. Furthermore, we found that the proportion of females was higher in the MVE than in the AVE group, which was also previously reported 11 21.…”
Section: Discussionsupporting
confidence: 90%
“…To better understand determinants of outcome, and to give a more precise understanding of native valve IE, patients with AVE and MVE should be studied separately. Previous studies on AVE and MVE have dealt with heterogeneous patient groups,10 11 including those with prosthetic valve IE and involvement of multiple valves. The aim of this study was to compare patient characteristics, microbiology, outcomes and predictors of mortality and surgery in patients with native valve IE involving either the aortic valve or the mitral valve.…”
Section: Introductionmentioning
confidence: 99%
“…Although the crude in-hospital case fatality rates observed are apparently similar to other reports, our patients were markedly younger. 2 28 Early mortality was mostly IE related due to cardiogenic shock and/or neurological complications. Mortality almost doubled at long-term follow-up, reaching 42.9%.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Evidence to date suggests that the pattern of infectious disease in patients with aortic valve involvement is diverse, possibly reflecting the heterogeneity in age, sex, pathogens implicated, prosthetic valve endocarditis (PVE), alongside clinical and surgical features. 1,2,[5][6][7] Surgical treatment of aortic valve endocarditis today is generally performed using conventional mechanical and stented xenograft prosthesis or cryopreserved aortic homograft while aortic valve repair is limited to well-circumscribed infectious injuries. 3,4,[8][9][10] However, the literature does not provide sufficient data for a systematic approach to AVE operations due to the lack of randomized trials classified as Class Ia level A or B, which may guide the timing and choices of the ideal substitute for infectious aortic valve disease.…”
Section: Introductionmentioning
confidence: 99%